2004
DOI: 10.1111/j.0361-3666.2004.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Health in Afghanistan: Results of a Knowledge, Attitudes and Practices Survey among Afghan Women in Kabul

Abstract: A reproductive-health knowledge, attitudes and practices (KAP) survey was carried out among 468 Afghan women of reproductive age. A convenience sample of women was selected from attendees in the outpatient departments of four health facilities in Kabul. Seventy-nine per cent of respondents had attended at least one antenatal consultation during their last pregnancy. Two-thirds (67 per cent) delivered their first child between 13 and 19 years. The Caesarean-section rate was low (1.6 per cent). Two-thirds (67 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 14 publications
5
61
0
1
Order By: Relevance
“…31 Two studies revealed that 83% and 75% of women respectively, expressed the view that it was a wife's duty/obligation to have sex with her husband even when she did not want to have sex. 9,10 In the same study, 93% of women said that they needed authorization from their husband or a male relative to seek professional health care. 10 In addition, published studies reported that that around half of the female respondents (45% and 56% respectively) reported that it was the right of a husband to beat his wife when she disobeys.…”
Section: Sociocultural Practicesmentioning
confidence: 92%
See 4 more Smart Citations
“…31 Two studies revealed that 83% and 75% of women respectively, expressed the view that it was a wife's duty/obligation to have sex with her husband even when she did not want to have sex. 9,10 In the same study, 93% of women said that they needed authorization from their husband or a male relative to seek professional health care. 10 In addition, published studies reported that that around half of the female respondents (45% and 56% respectively) reported that it was the right of a husband to beat his wife when she disobeys.…”
Section: Sociocultural Practicesmentioning
confidence: 92%
“…10 Women's education, irrespective of other socioeconomic factors, had positive contribution to improved reproductive health. 10 …”
Section: Ahmed Et Al Reported That In Westernmentioning
confidence: 99%
See 3 more Smart Citations